Translation Quality Analysis of Japanese Oral Translation (Tsuyaku) - Saragih, Febi Ariani; Solikhan, Hamim (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
The oral translation course at the Japanese Language Education Study Program, Universitas Brawijaya does not impose special requirements for students who want to take it. For this reason, this study aims to analyse the quality of studentâ€™s oral translations and to determine the competencies that affect the results of studentâ€™s Japanese-Indonesian oral translations. In the translation quality, special parameters are used as measurement tools, which are: accuracy, fluency, and clarity. Meanwhile, the parameters to determine the competence that affects the translation results using the bilingual sub-competence, extralinguistic sub-competence, nation translation sub-competence, instrumental sub-competence, strategic sub-competence, psychological sub-competence.Â Â Â This research uses descriptive qualitative method. The data used in this study were the transcripts of the results of the oral translation exercises from the audio â€œNihongo Soumatome Mondaiâ€Â that was played. The data collection technique uses primary and secondary sources. The analysis in this study used Miles and Huberman theory (reduction, data display, and verification). The result of accuracy parameter is inaccurate and the fluency parameter of the most translated result is fluent. In the clarity parameter, the highest number of translated results is non-acceptable. This shows that although students are fluent, their translation result are not acceptable. Meanwhile, the translation competence that affects the translation results of students who take theÂ tsuuyakuÂ course is the lack of a bilingual sub-competency factor or mastery of the source language of a translator. Although they already had the basics of translation before, however, due to the low bilingual sub-competence, no matter how well the translation theory has been mastered, it is still difficult to produce an accurate and clear translation.